THE EFFECTIVENESS OF GROUP INVESTIGATION-BASED DISCOVERY LEARNING MODEL WITH THE HELP OF CONCRETE OBJECTS ON STUDENT'S SCIENTIFIC THINKING ABILITY - Faninda Novika Pertiwi; Izza Aliatul Muna (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2021)
This study aims to describe the effectiveness of discovery learning model based on group investigation with concrete objects on students' scientific thinking skills. The type of research used in this case is an experiment with true experimental design and posttest only control design. This research was conducted to 60 students of class VIII SMPN 1 Jetis Ponorogo. This study used multiple choice tests and questionnaires as data collection instruments. The student test data were analyzed quantitatively using the two-tailed and one-tailed t-test. Based on the results of the two-tailed t test, the value of 0.011 <alpha was obtained, which means that there are differences in the scientific thinking ability of the experimental and control classes. Then from the results of the one-tailed t test, the value of 0.006 <alpha is obtained, which means H0 is rejected and H1 is accepted so can be concluded that the scientific thinking ability of experimental class students which use discovery learning and group investigation with concrete objects is better than the control class. This research can be used as a reference for educators in implementing active learning with discovery learning and group investigation models that can improve students' scientific thinking skill.